English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

Let 2x^2 - 23x = 0

x(2x - 23) = 0

Hence x = 0 or 2x - 23 = 0

x = 0 or x = 23/2 = 11.5

2007-05-25 12:06:32 · answer #1 · answered by dudara 4 · 0 0

2x^2-23x
x(2x-23) is all the factoring that can be done. If you meant that this equals zero then
x(sx-23)=0
x=0
2x-23=0
2x=23
x=11.5

x=0, 11.5

2007-05-25 12:19:22 · answer #2 · answered by yupchagee 7 · 0 0

2x^2-23x

x(2x-23)=0

x=0
2x-23=0
2x=23
x=11.5

2007-05-25 13:31:14 · answer #3 · answered by Dave aka Spider Monkey 7 · 0 0

factor out a x

x(2x-23)

i dont know what else you could do with that

2007-05-25 12:07:09 · answer #4 · answered by :) 5 · 0 0

fedest.com, questions and answers